miR-432-5p Inhibits the Ferroptosis in Cardiomyocytes Induced by Hypoxia/Reoxygenation via Activating Nrf2/SLC7A11 Axis by Degrading Keap1 - Wei Geng; Shaohua Yan; Xinyue Li; Qiumei Liu; Xuefei Zhang; Xinshun Gu; Xiang Tian; Yunfa Jiang (Analytical Cellular Pathology)
Early reperfusion into the myocardium after ischemia causes myocardial ischemia–reperfusion (I/R) injury and ferroptosis was involved. Ischemia activates the expression of a series of oxidative stress genes and their downstream regulatory genes, including ferroptosis-related genes such as nuclear factor E2-related factor 2 (Nrf2), glutathione peroxidase 4 (GPX4), and SLC7A11. This study adopted primary cardiomyocytes and I/R in rats to evaluate the ferroptosis and changing of Nrf2-SLC7A11/heme oxygenase-1 (HO-1) in vitro and in vivo. Online analysis tools were used to predict the possible target Kelch-like ECH-associated protein 1 (Keap1) of miR-432-5p. The mimic of miR-432-5p plasmid was constructed to verify the effect of miR-432-5p on ferroptosis. We found that hypoxia/reoxygenation (H/R) in cardiomyocytes and I/R in rats induced lipid peroxidation and ferroptosis in cardiomyocytes. The activation of the Nrf2-SLC7A11/HO-1 pathway protects cardiomyocytes from ferroptosis. Downregulation of miR-432-5p has been confirmed in H/R cardiomyocytes (in vitro) and cardiomyocytes in myocardial infarction rats (in vivo). Upregulation of miR-432-5p inhibited ferroptosis of cardiomyocytes induced by RAS-selective lethal 3 (RSL3), an inhibitor of GPX4 and ferroptosis inducer through decreasing the binding protein of Nrf2, Keap1, which was confirmed by bioinformatics and mutation assay. Knockdown Nrf2 attenuates the protection effect of miR-432-5p on H/R cardiomyocytes. Intravenous delivery of liposome carriers of miR-432-5p remarkably ameliorated cardiomyocyte impairment in the I/R animal model. In conclusion, miR-432-5p inhibits the ferroptosis in cardiomyocytes induced by H/R by activating Nrf2/SLC7A11 axis by degrading Keap1 and is a potential drug target for clinical myocardial infarction treatment.